2009
DOI: 10.1037/a0015084
|View full text |Cite
|
Sign up to set email alerts
|

A latent curve model of parental motivational practices and developmental decline in math and science academic intrinsic motivation.

Abstract: A longitudinal approach was used to examine the effects of parental task-intrinsic and task-extrinsic motivational practices on academic intrinsic motivation in the subject areas of math and science. Parental task-intrinsic practices comprise encouragement of children's pleasure and engagement in the learning process, whereas task-extrinsic practices comprise parents' provision of external rewards and consequences contingent on children's task performance. A conditional latent curve model was fit to data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 56 publications
3
71
1
6
Order By: Relevance
“…Results revealed that it did not. Gottfried et al (2009) showed that the more the parents used task-intrinsic practices, the less children showed a decrease in intrinsic motivation. These authors did not assess extrinsic motivation.…”
mentioning
confidence: 97%
“…Results revealed that it did not. Gottfried et al (2009) showed that the more the parents used task-intrinsic practices, the less children showed a decrease in intrinsic motivation. These authors did not assess extrinsic motivation.…”
mentioning
confidence: 97%
“…'' 3 A few years later, Barmby et al (2008) also established an inventory of their own (publications from 1975 to 2006) on the decline of attitudes and found 15 that reported a decline at the secondary level versus only one that recorded none, and four that reported a decline at the elementary level versus four that reported none. More recently, Gottfried et al (2009), citing seven more recent studies, wrote: ''Math and science are of particular concern because developmental decline in math and science motivation and attitudes has been a pervasive phenomenon across the literature.'' These reviews, although not encouraging, nevertheless give us a rather clear idea of the evolution of 2 It was also the one that had been increasingly used, recently.…”
Section: A Very Well-documented Decline With Age or School Yearsmentioning
confidence: 99%
“…Es importante que se considere, además de los factores cognitivos y lingüísticos, la influencia de factores motivacionales en la explicación y predicción del lenguaje escrito, en la línea que destacaban otros estudios sobre estas variables en el rendimiento académico en los primeros años de la educación secundaria (BarcaLozano, et al, 2012;Miñano, Gilar & Castejón, 2012;Gottfried et al, 2009). Las metas que el estudiante persigue en la realización de las tareas académicas, las creencias sobre la inteligencia y el modo de pensar ante una tarea, las atribuciones sobre los éxitos y fracasos, el sentimiento de autoeficacia, la percepción de dificultad, la utilidad de la realización de la tarea o la consecuencia externa, en definitiva, la motivación intrínseca y extrínseca, puede promover el esfuerzo y la persistencia en la tarea académica de leer y escribir, mejorar el rendimiento lectoescritor y disminuir sus dificultades (Guthrie et al, 2004).…”
Section: Discussionunclassified
“…La mayoría de estos estudios encuentran que las orientaciones hacia una meta y el interés por los aprendizajes escolares repercuten directamente en su rendimiento académico general y en el de diferentes áreas instrumentales como lengua y matemáticas. Destacan la importancia de las atribuciones de los éxitos y fracasos de los alumnos y del esfuerzo que llevan a cabo en la realización de las tareas académicas, como importantes determinantes del rendimiento escolar (Barca-Lozano, Almeida, Porto-Rioboo et al, 2012;Miñano, Gilar & Castejón, 2012;Gottfried, Marcoulides, Gottfried & Oliver, 2009). Barca-Lozano et al (2012) demuestran la importancia de variables motivaciones como las metas académicas de aprendizaje y las estrategias de autoeficacia, en el rendimiento escolar en alumnos de primer curso de la educación secundaria.…”
Section: Introductionunclassified